Microbiome Alterations in Patients with Chronic Prostatitis/Chronic Pelvic Pain Syndrome - Khan, Nouman; Bhatti, Muhammad Shahid; Chandio, Mumtaz Ali; Nawaz, Usama; Shahjehan, Shahjehan; Asghar, Hassan Raza; Sherjan, Syed Muhammad (Journal of Neonatal Surgery, 2025)
Background: Chronic Prostatitis/ Chronic Pelvic Pain Syndrome (CP/CPPS) is a widespread disease among men, featuring persistent pelvic discomfort and urinary symptoms in the absence of infection. Recent studies suggest that gut microbiota may influence systemic inflammation and pain signaling pathways, thus offering clues into the possible pathophysiology of CP/CPPS. ‘To compare the gut microbiome profile of patients with CP/CPPS to that of healthy individuals, and to explore possible associations with clinical symptoms and lifestyle factors’. Methods: A case-control study was carried out over the span of a year, from May 2023 to December 2024, with a sample size of 51 men. This included 26 patients diagnosed with CP/CPPS and 25 health matched controls. Relevant demographic information such as age alongside clinical history with symptoms severity scoring was captured systematically. Stool samples were gathered and analyzed via DNA sequencing for the 16S rRNA gene. Intergroup comparison of microbial diversity indices and taxonomic composition was carried out using appropriate statistical approaches. Results: Patients diagnosed with CP/CPPS exhibited decreased alpha diversity in comparison to the controls (Shannon index p = 0.004; Simpson index p = 0.006). In this group, increased relative abundance of Escherichia/Shigella together with decreased levels of some beneficial genera such as Lactobacillus and Faecalibacterium were noted. Such microbial changes were coupled with an increase in recent antibiotic use and lower fiber intake among patients. Conclusion: Patients with CP/CPPS exhibit signs of gut dysbiosis, marked by reduced microbial diversity and an imbalance in bacterial composition. These findings suggest a possible link between the gut microbiome and the persistence of pelvic pain symptoms, highlighting the potential of microbiome-targeted strategies in the management of CP/CPPS.